1991
DOI: 10.1177/039139889101400809
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Removal of IgE in Atopic Asthma by Extracorporeal Plasmoimmunoadsorption (EPIA): Development of a Clinical Adsorbent

Abstract: We have developed an immunoadsorbent (IA) for ex vivo removal of IgE after in vitro screening of matrix (Sepharose and tresyl-activated Toyopearl) and ligand (monospecific rabbit polyclonal anti-IgE antiserum and monoclonal antibodies (Abs) or their Fab fragments). Specific adsorptive capacity (SAC) for IgE was maximal in Sepharose-based IA with both types of Abs. Fab-containing IA on Sepharose retained 70-90% of the SAC of native Ab-containing IA. Toyopearl-based IA showed comparable SAC under static conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Anti‐IgE (the ligand used for removal of IgE from the extracorporeal circulation) binds IgE molecules with high affinity through interaction with Fab portion (antibody–antigen binding), whereas Lc probably binds through interaction with d ‐manose and d ‐glucose (21), with less specificity. The selectivity of anti‐IgE for total IgE was confirmed in vivo by specific adsorptive capacity for IgE from 83 to 98%, after 1200–3400 mL of processed pv (6). Some clinical IgE apheresis sessions were carried out for patients suffering from atopic asthma, containing high initial concentrations of IgE (6).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Anti‐IgE (the ligand used for removal of IgE from the extracorporeal circulation) binds IgE molecules with high affinity through interaction with Fab portion (antibody–antigen binding), whereas Lc probably binds through interaction with d ‐manose and d ‐glucose (21), with less specificity. The selectivity of anti‐IgE for total IgE was confirmed in vivo by specific adsorptive capacity for IgE from 83 to 98%, after 1200–3400 mL of processed pv (6). Some clinical IgE apheresis sessions were carried out for patients suffering from atopic asthma, containing high initial concentrations of IgE (6).…”
Section: Discussionmentioning
confidence: 90%
“…The selectivity of anti‐IgE for total IgE was confirmed in vivo by specific adsorptive capacity for IgE from 83 to 98%, after 1200–3400 mL of processed pv (6). Some clinical IgE apheresis sessions were carried out for patients suffering from atopic asthma, containing high initial concentrations of IgE (6). Although it produces good results and has efficiency, the Sepharose‐CL‐4B‐anti‐IgE is very expensive.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Actually, clinical studies performed with column‐bound anti‐IgE performed by Lebedin et al. (34) demonstrated that such a treatment is well tolerated and may reduce IgE levels.…”
Section: Discussionmentioning
confidence: 99%